An introduction to iOS programming : from getting the SDK to submitting your first app - Allan, Alasdair (O'Reilly, 2011)
"Learn the steps necessary for building your first iOS app. With this introductory video course, experienced iOS developer Alasdair Allan walks you through the entire process, from downloading the developer tools to submitting your finished app to Apple's App Store for sale. Ideal for beginning programmers, you'll work with Objective-C, Xcode, Cocoa Touch, and many other tools and techniques along the way."--Resource description page.